ANALYSIS OF SHOLAR HISTORY TEXTBOOKS- CASE STUDY ON SPANISH CIVIL POST WAR - Díez Gutiérrez, Enrique Javier (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2012)
The objective has been analyzing the text in History subject, specifically, analyzing the contents that are nowadays reflected on scholar textbooks in a specific history period of time of Spain, taking place in the Post war since 1939. The Franco Dictatorship Repression and Franco fight  lasted  begining the 60s. The corresponding contents at this period are located curricularly on the corresponding courses between 15 and 17 years old. The methodology used was qualitative using research instruments from the critical analysis of content and the teachers` interviews. After having done this lengthy study, we have found that thte History textbooks keep on ignoring or hiding facts that were developed after Republican failure experience in the 30s in Spain, specially the ones related to the Franco Dictatorship Repression and the resistance of many men and women in front of her. The findings of this research seem to remember what the Argentian writerJuan Gelman, victim of military didactorship, said: “The dictators dissapear and the organizers of oversight inmediately appear”.